Sarcasm in Anthony and Joe Russo’s Movie Avengers: Endgame - Syamsul Bahri; Dio Manik; Fadillah Fauziah Putri; Indi Azizah Nailah (Fonologi: Jurnal Ilmuan Bahasa dan Sastra Inggris, 2025)
Sarcasm is often used in movies to create humor, but it can also show deeper emotions like anger, disappointment, or hidden criticism. In the movie Avengers: Endgame, sarcasm is used by many characters to express their feelings and relationships in a funny but meaningful way. This research aims to analyze how sarcasm is used in the movie and to identify which types of sarcasm appear the most. The researcher used Elisabeth Camp’s theory, which divides sarcasm into four types: propositional, lexical, like prefixed, and illocutionary sarcasm. The method used is descriptive qualitative, by watching the movie, collecting sarcastic dialogues, and analyzing them based on the theory. The result shows that propositional sarcasm is the most used (43%), followed by lexical sarcasm (36%), illocutionary sarcasm (14%), and like-prefixed sarcasm (7%). From these findings, it can be concluded that sarcasm in Avengers: Endgame is not only for jokes but also helps to express the characters’ emotions, conflicts, and closeness, making the dialogue more interesting and meaningful for the audience.